Panorama do gerenciamento dos resíduos de construção e demolição no município de Limeira/SP - Oliveira, Leonardo Matheus de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
With the growth of cities, and population density, the generation of waste has increased exponentially in the last century, and continues to grow today, so it is increasingly necessary to raise awareness of the issue of Solid Waste, and public policies that create guidelines for your management. The National Solid Waste Policy assigns responsibilities to generators, consumers, and municipalities. The aspect of this work is the Construction and Demolition Waste, which was defined and classified for the first time in the country, in the Resolution 307/2002 from Conama, and presents a high percentage of the total generation of waste in the cities. In many municipalities, more than 50% of the total generation is Construction and Demolition Waste and therefore proper management and the existence of specific legislation are essential. The objective of the work was to understand the scenario of Construction and Demolition Waste in the municipality of Limeira/SP, verify its entire course, certify compliance with federal and municipal laws, propose guidelines for the optimization of the management of this type of waste, and also through the questionnaire answered by 214 municipalities in the state of São Paulo, to understand the management of this type of waste by the municipalities. With this research, it was possible to observe that the municipality of Limeira is supported by a Municipal Plan for Integrated Management of Construction and Demolition Waste and related legislation, however their applicability is not efficient, due to the lack of resources, and the non-implementation of management systems and advanced technologies. Therefore, this work identifies the situation in the municipality, and points out the importance of optimizing the management processes of this type of waste.

Com o crescimento das cidades, e o adensamento populacional, a geração de resíduos aumentou exponencialmente no último século, e continua crescendo hoje em dia, portanto se faz cada vez mais necessário uma conscientização sobre a temática de Resíduos Sólidos, e políticas públicas que criem diretrizes para o seu gerenciamento. A Política Nacional de Resíduos Sólidos – Lei 12.305/2010 atribui responsabilidades aos geradores, consumidores, e aos municípios. A vertente deste trabalho é o Resíduo de Construção e Demolição, que foi definido e classificado pela primeira vez no país, na Resolução Conama 307/2002, e apresenta elevado percentual da geração total de resíduos nas cidades. Em muitos municípios, mais de 50% da geração total, são Resíduos de Construção e Demolição e portanto o gerenciamento adequado e a existência de legislações específicas são essenciais. O objetivo do trabalho foi entender o cenário dos Resíduos de Construção e Demolição no município de Limeira/SP, verificar todo o percurso do mesmo, atestar o cumprimento das leis federais e municipais, propor diretrizes para a otimização do gerenciamento desse tipo de resíduo, e também através do questionário respondido por 214 municípios do estado de São Paulo, compreender o gerenciamento deste tipo de resíduo pelos municípios. Com esta pesquisa, foi possível observar que o município de Limeira está amparado um Plano Municipal de Gestão Integrada de Resíduos da Construção Civil e legislações relacionadas, no entanto a aplicabilidade das mesmas não se mostra eficiente, pela falta de recursos, e a não implantação de sistemas de gerenciamento e tecnologias avançadas. Portanto, este trabalho identifica a situação no município, e aponta a importância da otimização dos processos de gerenciamento deste tipo de resíduo.
Overview of construction and demolition waste management in the municipality of Limeira/SP
Keywords: Solid waste; Construction; Demolition; Waste; Municipality; Management; National waste policy; Resíduos sólidos; Gerenciamento de resíduos; Políticas públicas; Construção civil; Municípios; Política Nacional de Resíduos Sólidos; Resíduos de construção; Demolição